2020
DOI: 10.1007/s40201-019-00435-1
|View full text |Cite
|
Sign up to set email alerts
|

Microwave assist sorption of crystal violet and Congo red dyes onto amphoteric sorbent based on upcycled Sepia shells

Abstract: A new sorbent based on Sepia shells (cuttlefish bones) has been synthesized (SSBC) and tested for the sorption of cationic dye (crystal violet, CV) and an anionic dye (congo red, CR). SSBC was produced by reaction of sepia shells powder with urea in the presence of formaldehyde. In the first part of the work, the sorbent was characterized using scanning electron microscopy, energy dispersive X-ray analysis, Fourier-transform infra-red spectrometry and titration (for determining pH PZC ). In a second step, sorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(22 citation statements)
references
References 97 publications
0
22
0
Order By: Relevance
“…2, the sorption capacity predicted by the PSORE decreases with increasing the respectively). The enhancement of mass transfer properties in microwave-assisted sorption properties was already reported for the removal of metal ions [102,103] and dyes [64]. Contact times as short as 30-60 s were reported as sufficient for reaching equilibrium [64,103].…”
Section: 231mentioning
confidence: 71%
See 2 more Smart Citations
“…2, the sorption capacity predicted by the PSORE decreases with increasing the respectively). The enhancement of mass transfer properties in microwave-assisted sorption properties was already reported for the removal of metal ions [102,103] and dyes [64]. Contact times as short as 30-60 s were reported as sufficient for reaching equilibrium [64,103].…”
Section: 231mentioning
confidence: 71%
“…The enhancement of mass transfer properties in microwave-assisted sorption properties was already reported for the removal of metal ions [102,103] and dyes [64]. Contact times as short as 30-60 s were reported as sufficient for reaching equilibrium [64,103]. Mahmoud et al [102,103] identified both the effect of increased temperature and diffusion enhancement as the major causes of sorption enhancement.…”
Section: 231mentioning
confidence: 84%
See 1 more Smart Citation
“…Different materials have been reported for the adsorption of dyes between them magnetite nanoparticles [ 5 ], urea calcium alginate xerogel beads [ 6 ], metal/mineral materials such as CuO, zinc, iron, and zeolite [ 7 ]. Bioadsorbents have also been used as bivalve shells of anadara uropigimelana [ 8 ], sepia shells (cuttlefish bones) [ 9 ], to fabricate monolithic algal green powder (MAGP) based on the marine green macroalga enteromorpha flexuosa [ 10 ] as well as magnetically modify products of the coffee industry [ 11 ]. Nowadays, methodologies based on energy sources such as microwave or ultrasound radiation are exploited to accelerate different sorption processes.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption mechanism is based in the capture or retention of a compound (adsorbate) in a liquid phase by a solid (adsorbent) (Mostafa et al , 2009; Park et al , 2010). In this sense, a wide range of low-cost materials have been studied to be used as potential adsorbents for dyes such as wood (Kelm et al , 2019; Naeem and Hassan, 2018), clay (Kausar et al , 2018), ashes (Mor et al , 2018), activated muds (Qu et al , 2012; Sarvajith et al , 2018), orange (Namasivayam et al , 1996), cuttlefish bones (Elwakeel et al , 2020), algae (Elgarahy et al , 2020) and banana peels (Temesgen et al , 2018). In these recent years, the concepts of reuse and recycling have taken an important role in our society and resulted in an increase in research and development in sustainable technologies.…”
Section: Introductionmentioning
confidence: 99%